Country risk assessment model for four ASEAN countries - Lee, See Nie; Cheng, Fan Fah; Chowdury, Taufiq Hassan Shah (2015)
This paper aims to investigate country risk by using the Two-Limit Tobit Model. This study begins by identifying empirically the important factors affecting the debt service capacity of borrowing countries. In this study we assess the riskiness of four developing countries in ASEAN over the period of 1970 to 2013. In this model, a quarterly-ahead debt rescheduling ratios are used as the dependent variable. Using the debt rescheduling ratios, we emphasize the role of relative sizes of debt rescheduling in predicting external debt crisis. A special emphasis is given to the seven crises, namely, the World Oil Crisis (1973-74), IMF Crisis (1976), Crisis of 1982, Black Monday 1987, the Saving and Loan Crisis (early 1990s), the Asian Financial Crisis (1997) and the Mortgage Crisis (2007) and their predictability. The final results show that Malaysia, the Philippines and Thailand have country risks that are highly affected by the crisis.